2010
DOI: 10.3350/kjhep.2010.16.4.405
|View full text |Cite
|
Sign up to set email alerts
|

A case of hepatocellular carcinoma in the caudate lobe successfully treated by transcatheter arterial chemoembolization using drug-eluting beads

Abstract: Hepatocellular carcinoma (HCC) in the caudate lobe remains one of the most intricate locations where various treatments tend to pose problems with regard to the optimal approach. Surgical resection has been regarded as the most effective treatment; however, isolated resection of the caudate lobe is strenuous and associated with a high rate of early recurrence. Percutaneous ablation might be technically difficult or impossible to perform due to the deep location of tumors and adjacent large vessels. Treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…TACE has been utilized for the treatment of caudate lobe HCC but can be technically difficult for interventional radiologists. [5] e reported technical success rate for selective caudate lobe TACE is 71% with local recurrence at 77%. [6] e difficulties with both interventional and surgical treatments for caudate disease lead to its poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TACE has been utilized for the treatment of caudate lobe HCC but can be technically difficult for interventional radiologists. [5] e reported technical success rate for selective caudate lobe TACE is 71% with local recurrence at 77%. [6] e difficulties with both interventional and surgical treatments for caudate disease lead to its poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[6] e difficulties with both interventional and surgical treatments for caudate disease lead to its poor prognosis. [5] While proximal occluding catheters are commonly used to perform embolization in TACE and TARE, the utilization of distal occlusion for proximal delivery is rare [7] However, in caudate HCC disease, arterial supply has a propensity for complex origins. For example, Yoon et al reported two direct proper hepatic arteries supply in 175 caudate lobe HCC cases.…”
Section: Discussionmentioning
confidence: 99%